PROSPECTS FOR OBTAINING BIOSTIMULANTS BASED ON FERROCENE - Ibrohim Asqarov; Qobiljon Otakhonov; Gayratjon Madrahimov; Hadyatillo Iminov; Kamoliddin Abdullajonov (Western European Studies, 2024)
The article provides information on the production of ferrocene and biologically active compounds synthesized on its basis, their physicochemical properties, practical significance, and influence on the growth, development and yield of plants. Data on the synthesis of oferrocenyl benzoic acid, its structure and chemical composition are also provided
Keywords: ferrocene; biologically active; cyclopentadienyl ring